Exploring Analytical Quality by Design (AQbD) Enabled RP-HPLC Method for Carvedilol - Randive, Krantisinha Hanumant; Maste, Meenaxi Maruti; Kempwade, Amolkumar Ashok (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Carvedilol (CDL) is a beta-blocker that helps to lower the risk of heart attack related mortality and is used to treat congestive heart failure and excessive blood pressure. Objectives: The present study deals with the development and validation of a reverse-phase high performance liquid chromatography method for rapid and reliable analysis of CDL by utilizing the Analytical Quality by Design (AQbD) approach. Materials and Methods: Critical Analytical Attributes (CAAs) were selected based on predefined Analytical Target Attributes (ATPs). Further screening of Critical Material Attributes (CMAs) and Critical Process Parameters (CPPs) having a significant impact on assigned CAAs was done by Taguchi Design. The optimized mobile phase consists of 0.1% Orthophosphoric Acid (OPA) and methanol in a ratio of 35:65% v/v. The flow rate was maintained at 1 mL/min, the column temperature was 30ºC, and the analysis was carried out at 240 nm. Based on the results obtained, fine tuning of the CAAs was done by opting for the 32-Box-Behnken design. Results: The area under the curve was found to be linear within the studied range of 5-30 μg/mL (R2=0.999). The retention time was found to be 4.18 min, with a sharp, well-defined peak. The percentage recovery of the drug during the accuracy study was found to be in the range between 97.06 and 99.29%. The detection and quantification limits were found to be 0.61 μg/mL and 1.86 μg/mL, respectively. Conclusion: The developed method was found to be precise with a RSD of <1%. The method can be effectively utilized for routine analysis of bulk drug and dosage forms in quality control labs.
Keywords: Analytical Quality by Design; Carvedilol; RP-HPLC; Box-Behnken design; Taguchi; Design